Impact of irrigation schedules and mulch on productivity and moisture extraction pattern of linseed (Linum usitatissimum): IMPACT OF IRRIGATION AND MULCH ON PRODUCTIVITY AND MOISTURE EXTRACTION OF LINSEED - S SARKAR; A SARKAR (Journal of Oilseeds Research, 2017)
A field experiment was conducted during rabi 2010-11 and 2011-12 to evaluate the effect of irrigation and mulch on seed yield, oil yield and water use of linseed. Linseed irrigated at IW/CPE of 0.6 showed 6.72 and 17.63 per cent higher seed yield compared to IW/CPE of 0.4 (669 kg/ha) and rainfed (607 kg/ha), respectively and was significantly superior. Maximumseed yield of about 707 kg/ha under the treatment receiving black polythenemulch, which was about 4.33, 8.72 and 14.76 per cent higher over the treatments receiving straw @ 5 t/ha, water hyacinth @ 5 t/ha and no mulch, respectively. Maximum oil yield was registered by the crop irrigated at IW/CPE of 0.6 and treatment receiving black polythene mulch. Water use efficiency was highest with rainfed treatment and that receiving black polythene. The significant increase in seed yield has led to increase in water productivity ofthe crop. Linseed extracted maximum soil moisture at its grand growth stage. The treatment combination receiving irrigation at IW/CPE of 0.6 along with black polythene mulch maintained its superiority with highest net return and B:C ratio and proved as best treatment combination.